2017
DOI: 10.1002/mrm.26699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concentration and vendor specific composition of formalin on postmortem MRI of the human brain

Abstract: Our study demonstrates that differences of the formalin composition have substantial effects on MRI signal characteristics after fixation, which can explain the divergence of reported relaxation times beyond the effect of differences in formalin concentration. Magn Reson Med 79:1111-1115, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
(42 reference statements)
3
27
0
Order By: Relevance
“…NMR parameters that modulate the image contrast strongly depend on the specimen preparation even if the preparations are supposedly the same. Namely, it is well known that the relaxation properties of fixed tissue depend on the tissue history, local conditions, and fixative origin and concentration . Also, we have shown that the T 2 relaxation time in fixed tissue depends on the concentration of salt and buffer in formalin fixative .…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…NMR parameters that modulate the image contrast strongly depend on the specimen preparation even if the preparations are supposedly the same. Namely, it is well known that the relaxation properties of fixed tissue depend on the tissue history, local conditions, and fixative origin and concentration . Also, we have shown that the T 2 relaxation time in fixed tissue depends on the concentration of salt and buffer in formalin fixative .…”
Section: Discussionmentioning
confidence: 51%
“…Namely, it is well known that the relaxation properties of fixed tissue depend on the tissue history, 39 local conditions, 49 and fixative origin and concentration. 40 Also, we have shown that the T 2 relaxation time in fixed tissue depends on the concentration of salt and buffer in formalin fixative. 41 Most likely there are also other parameters (e.g.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has previously been shown that adding 4% formaldehyde to PBS markedly shortens T 2 relaxation, and washing out bulk fixative from thin rat cortical slices (fixed for ~10 days) restores T 2 relaxation times to typical in vivo values . It has also been suggested that different brands of formalin solution might exhibit differential magnetostatic properties . Conceivably, therefore, the strong paramagnetic moments observed in some—but not all—formalin preparations might not originate from formaldehyde but from other chemical substances present in the mixture.…”
Section: Discussionmentioning
confidence: 99%
“…14 It has also been suggested that different brands of formalin solution might exhibit differential magnetostatic properties. 54 Conceivably, therefore, the strong paramagnetic moments observed in some-but not all-formalin preparations might not originate from formaldehyde but from other chemical substances present in the mixture. Our results were consistent with previous findings in that we also observed a steep reduction in R 2 * after washing out formalin with PBS which was, however, not accompanied by a corresponding QSM offset, but by a decrease in QSM variability.…”
Section: Discussionmentioning
confidence: 99%